Enabling secure and resource-efficient blockchain networks with VOLT - Setty, Srinath; Basu, Soumya; Zhou, Lidong; Stephenson, Justine; Venkatesan, Ramarathnam (Microsoft, 2017)
This paper describes VOLT, a permissioned blockchain network for a group of autonomous organizations to automate cross-organizational business processes. Specifically, VOLT ensures that a correct member—without trusting anyone else—shares a consistent history of transactions with other members in the system. VOLT achieves this strong security property using the concept of a self-verifying ledger: an append-only ledger of transactions that can be checked locally by a verifier process at each node; the ledger also embeds succinct cryptographic messages encoding views of members to enable each verifier to locally determine globally-committed transactions. To orchestrate this concept, VOLT employs a logically centralized—but untrusted—service provider. We instantiate the service provider using a highly-available cloud service built atop a fault-tolerant cloud storage service. An experimental evaluation of our implementation demonstrates that VOLT achieves tens of thousands of transactions per second for a realistic 50-node payment network.